What happened to hannah ebook A novel. - McComas, Mary Kay (2024)
As a teenager, Hannah Benson ran away from home in order to save herself. Now, twenty years later, the past comes calling and delivers life-changing news: her mother and sister have passed away, leaving Hannah the guardian of her fifteen-year-old niece. Returning home to bitter memories and devastating secrets, Hannah must overcome her painful past to pave a future with her niece, the last best chance at a family for both of them. She begins to create a new, happier life with her niece and rekindles a relationship with Grady Steadman, one of the few people she’s ever called a friend. But she can’t forget what she cannot forgive, or lay to rest those ghosts that will not die. Will love and trust—and the truth—give her the strength to stand her ground and fight for what she deserves?